2021
DOI: 10.1111/jce.14914
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of two versus three incision techniques: Results from the subcutaneous ICD post‐approval study

Abstract: Background Traditionally, implantation of the subcutaneous implantable cardioverter defibrillator (S‐ICD) requires incisions near the lateral chest wall, the xyphoid, and the superior sternal region (three‐incision technique [3IT]). A two‐incision technique (2IT) avoids the superior incision and has been shown to be a viable alternative in small studies with limited follow‐up. Objectives To report on the long‐term safety and efficacy of the 2IT compared to the 3IT procedure in a large patient cohort. Methods P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 14 publications
(31 reference statements)
4
15
0
Order By: Relevance
“…This hypothesis did not align with our findings, which revealed no statistically significant difference between the two groups in lead dislocation, inappropriate shocks, defibrillation test failure, and first shock efficacy. Our findings match the results of previous studies by El Chami et al., Stuijt et al., and Brouwer et al 17,18,21 . Brouwer et al 21 .…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…This hypothesis did not align with our findings, which revealed no statistically significant difference between the two groups in lead dislocation, inappropriate shocks, defibrillation test failure, and first shock efficacy. Our findings match the results of previous studies by El Chami et al., Stuijt et al., and Brouwer et al 17,18,21 . Brouwer et al 21 .…”
Section: Discussionsupporting
confidence: 93%
“…The omitted incision also carries a low anatomical risk as it is far from any neurovascular structures. 17 A previous study reported 4 of 7 infections to occur in the xiphoid incision. 5 Therefore, the findings of our meta-analysis reflect a real effect, as the upper parasternal incision does not carry a high risk of infection.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…This latter finding has been related to distal lead malposition, due to its migration in absence of a suture or to an improper placement in absence of direct visualization by the implanting physician. However, another study 16 demonstrated that the two techniques did not show significant differences in terms of mortality rates, shock efficacy, defibrillation testing, IASs, and surgical wound complications, but the two-incision technique shortened procedural times.…”
Section: Discussionmentioning
confidence: 96%